Pro-poor biotechnology and biosafety research in partnership with developing countries: An overview of current IFPRI initiatives - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
The majority of poor people in developing countries rely on agriculture for their food and livelihoods. However, they are increasingly vulnerable and food insecure due to declining agricultural productivity growth, climate change susceptibility, and volatile food and energy prices. As part of its commitment to improving livelihoods and reducing poverty, IFPRI is undertaking substantial work on food- and nutrition-related science and technology policy, with an emphasis on innovations that are relevant, safe, and accessible to poor people. Assessing the socioeconomic opportunities and risks of agricultural biotechnology for smallholder farming systems, poor consumers, biodiversity, and trade is a priority on IFPRI’s research agenda. IFPRI’s biotechnology research is also complemented by its work on biosafety policy issues.